Metode Menafsirkan Kata Amar dan Nahi dalam Al-Qur’an: Kaidah dan Kandungan Makna Amar dan Nahi - Abd. Muqit (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
This research This research is research that uses the research library method. This research The method used in this research is the descriptive method, namely research that only describes the research results that the researcher obtained in exploring the data. After that, research validates the data and then abstracts it in the form of written work. The results of this research conclude that the meaning of Amar is that there is something essential and something majestic. Amar's true meaning is only obligatory. while amar majazi has many meanings, namely Amar which means sunnah, irsyad, mubah, ta'dib, indzar and prayer. Meanwhile, the meaning of nahi is essence and majazi. The true meaning of amar is that it is only obligatory. Meanwhile, the majazi meaning of nahi is makruh, prayer, irshad, tahqir, aqibah, ta'yis, tahdid, iltimas, and syufqah. Meanwhile, the rule of Amar is that first Amar does not have to be repeated unless there is a qorinah that requires it to be repeated. Both rooms do not have to be done immediately unless there is a Korina that requires it to be done immediately. When Amar must follow the qayyid that accompanies Amar, it either includes the time to carry out Amar or the order to be carried out immediately. Meanwhile, the rule is that first nahi applies and so on unless there is a qorinah that limits it. The nullity of a prohibited law depends on the prohibition if the prohibited substance is the law. Likewise, the law is void if the prohibition is of a nature that determines what is forbidden. But when what is prohibited is due to something else, the law is not invalidated.